The Effectiveness of internet Cognitive Behaviour Therapy (iCBT) For Depression: A systematic review: Effectiveness of internet Cognitive Behaviour Therapy (iCBT) For Depression: A systematic review - Abdan Syakura; Edy Suryadi A (International Journal of Nursing and Health Services (IJNHS), 2021)
Background. Lack of society in seeking treatment of depression still occurs in society. This is influenced by the limitations of psychological face-to-face treatment, stigma, limited medical expenses and limited therapists. Aims. The purpose of this study to determine the effectiveness of Internet Cognitive Behavior Therapy (iCBT) on reducing depression. Method. This study was systematic review of depressed patients with study selection criteria using Scopus, Science Direct, and Pubmed databases by Randomized Control Trial (RCT). Results. A total of 15 relevant articles were reviewed in this study. The findings showed that the iCBT has positive effect on decreasing the depression. It was due to iCBT therapy could control the mood of people. Conclusion. This systematic review is aimed to explore increasing the use of technology and information support in providing nursing care to clients to reduce depression